Mindset change: Prerequisite for academic excellence at the North West University, Mafikeng Campus - Makondo, Livingstone (South African Journal of Higher Education, 2016)
This article submits that the calibre, attitude and mindset of lecturers/teachers in institutions of Higher Education need drastic improvement and change if academic excellence is to be attainable and sustained in the 21st century. This article builds on the observations by Makondo (2010.263-276) that most university teaching staff members are consciously or otherwise, playing significant roles in their students’ academic underperformance due to their failure to effectively deliver their lectures and examine their learner’s performance. This discussion notes that diverse factors account for student underperformance and proceeds by submitting that the calibre, attitude and mindset of lecturers is one such core factor which calls for urgent exploration. Cases in point are the failure of the majority of university graduates to produce convincing passing results from matric and university students, an unacceptable trend as the governments, parents/guardians and donors alike are heavily investing in education. Also, the prevalent trend that undergraduate and postgraduate students require second or third chances to complete their studies says a lot about the challenges rampant in the Higher Education system. Insights for this participatory expository research came from questionnaires, secondary literature and the researcher’s experiences as an educator in high schools and universities in Zimbabwe and South Africa. Among others, to circumvent the seeming challenges, this study submits that Academic Development Centres (ADC) or Centres for Academic Excellence (CAC) or Centres for Higher Education (CHE) or their equivalent departments have strategic supportive roles to ensure that lecturers are fully empowered to execute their core teaching and research activities. Among other pragmatic ways forward, lecturers need to be lifelong researchers as can be testified by their research publication output and NRF rating so that they would be abreast with knowledge changes in their diverse areas of specialties.